Error Analysis in Students' Recount Text Writing: A Study of Papuan EFL Learner - Siti Maria Ulfa Mattarima; Irma Juliana Ekawati Janis; Sunengko (Qalam : Jurnal Ilmu Kependidikan, 2026)
This study investigates the types and sources of errors in students’ recount text writing. Using a qualitative descriptive design supported by quantitative data, ten texts produced by EFL students were analysed through an error analysis framework in Applied Linguistics. The analysis focused on identifying, classifying, and explaining learners’ errors. The findings reveal approximately 300 errors, categorized into grammatical (40%), syntactic (23%), lexical (15%), spelling (13%), and mechanics errors (9%). Grammatical errors were the most dominant, particularly in the misuse of past tense, verb forms, and articles. Syntactic errors involved sentence structure and word order, while lexical errors reflected inappropriate word choice and first language interference. Spelling and mechanics errors, though less frequent, still affected overall writing quality. The study also found that errors were mainly caused by overgeneralization, first language interference, incomplete rule application, and carelessness. These findings indicate that students are still developing their linguistic competence, especially in grammar and sentence construction. The study suggests the need for focused instruction on past tense, sentence structure, and contextual vocabulary, as well as the integration of revision and self-editing strategies to improve students’ writing performance. Keywords: error analysis, EFL writing, recount text, grammatical errors, applied linguistics